Effect of antibiotics on toxin production and viability of Clostridium perfringens. - Stevens, D L (1987)
We have recently reported (D.L. Stevens, K.A. Maier, B.M. Laine, and J.E. Mitten, J. Infect. Dis. 155:220-228, 1987) that clindamycin, rifampin, and tetracycline were more efficacious than penicillin in the treatment of fulminant gas gangrene in mice caused by Clostridium perfringens. We hypothesize that antibiotic efficacy correlated with bactericidal or toxin-suppressing properties of these agents. To investigate the possibility that penicillin is only bacteriostatic against C. perfringens, we performed macrobroth dilution MIC and MBC determinations using C. perfringens ATCC 13124. Mean MICs were equal to MBCs for the following antibiotics (micrograms per milliliter): clindamycin, 0.07; tetracycline, 0.05; rifampin, 0.03; metronidazole, 0.69; and penicillin, 0.27. The MIC/MBCs of chloramphenicol were 1.50/3.10 (micrograms/ml). Because antibiotic efficacy did not correlate with bactericidal activity, we measured alpha-toxin activity and found complete suppression of alpha-toxin activity by tetracycline, metronidazole, rifampin, clindamycin, and chloramphenicol at concentrations equal to the MIC. In contrast, alpha-toxin activity persisted at concentrations of penicillin equal to and above the MIC. The dynamics of bacterial killing and kinetics of alpha-toxin production were next studied in log-phase cultures of C. perfringens with antibiotic concentrations 10 times the MIC. Clindamycin, metronidazole, and rifampin all caused rapid reductions in viability, turbidity, and alpha-toxin activity by 15 to 45 min. In contrast, penicillin demonstrated slower bacterial killing, increased turbidity (62.6% of control), and persistent alpha-toxin activity (80% of control values) for 2 h. Tetracycline and chloramphenicol were the least effective in reducing viability; however, the turbidity of cultures did not increase, and alpha-toxin activity was not detectable. Toxin suppression and rapid bacterial killing may in part explain the observed superior therapeutic efficacy of clindamycin, rifampin, and metronidazole compared with penicillin in the treatment of experimental gas gangrene.